Circular economy in Mexico: sucess stories and challenges facing COVID-19 - Gómez - García, César René (Universidad Francisco de Paula Santander, 2024)
The objective of this research work was to analyze the development of the circular economy in Mexico in the context of COVID-19, understanding that the experience put in the spotlight the need to reconfigure the processes in the use of energy, water supply, pollution control and production of Mexican companies. For this work we used a qualitative methodology of descriptive and documentary character of the economic situation of the country, so it was possible to appreciate those companies that have implemented the application of the circular economy. This analysis allowed us to discuss advances and particular situations of the study, observing that there is a great area of opportunity derived from the circular economy applied in the Mexican territory, which led to a reflection on the growing interest in the circular economy in Mexico and in the efforts to promote it by the companies, with a view to favoring the environment and innovating in the way in which their production processes are carried out.